1998
DOI: 10.1088/0268-1242/13/11/002
|View full text |Cite
|
Sign up to set email alerts
|

Strained-Si heterostructure field effect transistors

Abstract: The purpose of this review article is to report on the recent developments and the performance level achieved in the strained-Si/SiGe material system. In the first part, the technology of the growth of a high-quality strained-Si layer on a relaxed, linear or step-graded SiGe buffer layer is reviewed. Characterization results of strained-Si films obtained with secondary ion mass spectroscopy, Rutherford backscattering spectroscopy, atomic force microscopy, spectroscopic ellipsometry and Raman spectroscopy are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(65 citation statements)
references
References 117 publications
(208 reference statements)
1
64
0
Order By: Relevance
“…We can see that the drain current and the transconductance are improved about 2.7 and 3.1 times respectively by using the stained-Si channel. The hole mobility enhancement factor due to 1% strain in Si is about 1.5 [12]. Therefore, the drivability improvement is mainly attributed to the hole SBH reduction between source and channel.…”
Section: Devices Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…We can see that the drain current and the transconductance are improved about 2.7 and 3.1 times respectively by using the stained-Si channel. The hole mobility enhancement factor due to 1% strain in Si is about 1.5 [12]. Therefore, the drivability improvement is mainly attributed to the hole SBH reduction between source and channel.…”
Section: Devices Fabrication and Characterizationmentioning
confidence: 99%
“…On the other hand, the strained-Si channel MOSFET has also received a great deal of attention recently due to its improved mobility [12]. A key processing issue to fabricate the strained-Si MOSFET is the low thermal budget to prevent strain relaxation and dislocation propagation from the buffer layers during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Strained-Si technology offers device designers the ability to enhance carrier mobility and modify the band gap, which is compatible with the existent Si device process. Recently, research about this strain engineering has been reported [1][2][3][4][5][6][7].Reports on the threshold voltage model of strained-Si metal-oxide-semiconductor field-effect transistor (MOSFET) can be found [3]. However, there has been no research done on this device regarding the subthreshold current, which is one of the main parts of power consumption in deep submicron integrated circuits.…”
mentioning
confidence: 99%
“…Strained-Si technology offers device designers the ability to enhance carrier mobility and modify the band gap, which is compatible with the existent Si device process. Recently, research about this strain engineering has been reported [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…A few percent strain can increase the electron mobility µ in silicon by a factor of three [57][58][59], while at the same time the subthreshold current may . .…”
Section: Strain and Subthreshold Currentmentioning
confidence: 99%